Challenges characterizing N deposition to high elevation protected areas: A case study integrating instrument, simulated, and lichen inventory datasets for the Devils Postpile National Monument and surrounding region, USA. (March 2021) - Jovan, Sarah; Fenn, Mark E.; Buhler, Monica; Bytnerowicz, Andrzej; Kovasi, Adrienne; Hutten, Martin; DiMeglio, Elisa; Schweizer, Donald
Graphical abstract: Highlights: Management of federal protected lands often requires fine-scaled N data. Simulated N diverged considerably from measured deposition. Divergences were due to difficulty modeling dry N deposition. Lichen assays reflected deposition heterogeneity. Development of indicators for high elevations is needed. Abstract: Excess N deposition is a common stressor of ecological health. Sensitive biota, including many lichens, respond to small differences in atmospheric N deposition. For lands with a conservation mandate, obtaining sufficient N data to evaluate risks is a challenge, especially in Mediterranean or arid landscapes. Managers in the Western U.S. commonly use epiphytic ("tree-dwelling") lichens to supplement N assessments, although options for higher elevations lacking epiphytes are poorly developed. Managers instead rely on broad-scale air quality simulations like the Total Deposition Model (TDEP). The Sierra Nevada Range is an example where anthropogenic N reaches mid-to-high elevation protected areas but managers lack tools for monitoring at ecologically relevant spatial-scales. Our main goals were to demonstrate how well-studied epiphytic bioindicators can supplement N assessments and recommend saxicolous ("rock-dwelling") candidates for similar development to improve coverage in higher elevations. As a case study, we characterized N deposition at a small (323 ha) protected area, Devils Postpile National Monument (DEPO), by integrating data from TDEP, air instruments, and assays of %N in the epiphyte Letharia vulpina . We used the regional N threshold associated with detrimental effects to epiphytic lichen communities, 2.9 kg N ha −1  yr −1 in throughfall (i.e. under a tree canopy), as a provisional critical load (CL) for indicating areas at risk of ecological impacts. Results clearly showed the need for empirical, diverse, and finer-scaled information, even for an area as small as DEPO. Importantly, simulations from TDEP overestimated dry deposition of oxidized N, making total N estimates nearly twice measured values (6.0 vs 3.03 – 3.66 kg N ha −1 yr −1, respectively). While small, our L. vulpina dataset (n = 5) from the Monument indicated highly variable N in throughfall (1.7 – 4.44 kg N ha −1 yr −1 ), with small-scale drivers, like proximity to the river canyon and the Central Valley, tipping the scale towards CL exceedance. Regional L. vulpina assays (n = 355) showed a distinct north-to-south gradient in California where N deposition at DEPO was highly similar to the nearby protected area, Yosemite National Park, where ecological impacts of excess N are well-documented. To expand N bio-monitoring into higher elevation areas, we recommend vetting five widespread saxicolous species, Rhizoplaca melanophthalma, Umbilicaria phaea, U. polaris, Xanthoparmelia coloradoënsis, and X. cumberlandia.